Chemotactic Zn micromotor for treatment of high blood ammonia-associated hepatic encephalopathy - Ye Feng; Chao Gao; Xiuyun Peng; Bin Chen; Miaomiao Ding; Dailing Du; Jinghui Rong; Qi Lv; Daniela A. Wilson; Yingfeng Tu; Fei Peng (Nature Communications)
Abstract Hepatic fibrosis involves hepatocyte damage, causing blood ammonia accumulation, which exacerbates liver pathology and crosses the blood-brain barrier, inducing hepatic encephalopathy. It is meaningful to construct a therapeutic platform for targeted ammonia clearance. In this work, a biocompatible water-powered Zn micromotor is constructed as an ammonia chemotaxis platform, which can be actuated by the water splitting reaction and the self-generated Zn2+ gradient. It can propel towards NH3·H2O source through the formation of complex ions [Zn(NH3)1](OH)+ and [Zn(NH3)2](OH)+, representing a generalizable chemotaxis strategy via coordination reaction. In vivo, biomimetic collective behavior allows precise navigation and reduction of the intrahepatic ammonia level, reshaping the pathological microenvironment. This mechanism, operating in a green, zero-waste manner, facilitates integration of these micromotors into the domain of biological regulation. Such environment environment-adaptive platform is favorable for targeted treatment of hepatic fibrosis and hepatic encephalopathy caused by hyperammonemia, which is expected to provide inspiration for future personalized and precision medicine.